Utilization Of Tobacco Stem (Nicotiana tabaccum L) As Tray Egg Filler - Andrew Setiawan Rusdianto; Winda Amilia; Fatma Dewi (Food, Agriculture and Natural Resources - NETWORKS, 2020)
Generally only used the leaves of tobacco plants as raw material for cigarette and stems discarded as waste. The use of waste tobacco rod has the potential to be converted into primary packaging such as trays range chicken eggs because it has a high cellulose content. Tobacco rod contains a relatively high amount of cellulose, reaching 56.10 percent of dried tobacco stalks. The process is done in making pulp fiber or tobacco stem malalui process of alkali (NaOH) with specific concentration to produce pulp that is good. The use of NaOH aims to degrade lignin by means of partial overhaul of bond. The existence of lignin in the pulp generally unfavorable effect on the quality of pulp for fiber becomes rigid, Statistical data analysis using ANOVA If treatment showed differences do a further test using Duncan's Multiple Range Test (DMRT) at significance level of 5 percent. The data generated is the highest grammage at 5 percent NaOH treatment amounted to 201.1 g.m-2 and the lowest 15 percent NaOH treatment 132.8 g.m-2, the highest thickness of 5 percent NaOH treatment of 2.509 mm and the lowest 15percent NaOH treatment of 1,835 mm. The highest density of 5 percent NaOH treatment of 80.81 kg.m-3 and the lowest at 10 percent NaOH treatment of 57.61 kg.m-3. While the highest tensile resistance in the treatment of 10percent NaOH 76.27 N.m-1 and the lowest at 5 percent NaOH treatment is 45.82 N.m-1, the highest thickness of 5percent NaOH treatment of 2.509 mm and the lowest 15 percent NaOH treatment of 1,835 mm. The highest density of 5 percent NaOH treatment of 80.81 kg.m-3 and the lowest at 10 percent NaOH treatment of 57.61 kg.m-3. While the highest tensile resistance in the treatment of 10 percent NaOH 76.27 N.m-1 and the lowest at 5 percent NaOH treatment is 45.82 N.m-1, the highest thickness of 5 percent NaOH treatment of 2.509 mm and the lowest 15 percent NaOH treatment of 1,835 mm. The highest density of 5 percent NaOH treatment of 80.81 kg.m-3 and the lowest at 10 percent NaOH treatment of 57.61 kg.m-3. While the highest tensile resistance in the treatment of 10 percent NaOH 76.27 N/m and the lowest at 5 percent NaOH treatment is 45.82 N.m-1